THE IX-XII CENTURIES RENAISSANCE SCIENTIFIC DISCOVERIES IN MATHEMATICS AND ASTRONOMY - Teshaboyeva Nafisa Zubaydulla qizi,; Solnishkina Marina Ivanovna,; Erkinova Muqaddas Olim qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The Central Asian Renaissance, spanning from the 9th to the 12th centuries, represents a monumental era of intellectual awakening that transformed the cultural and scientific landscape of the medieval world. During this epoch, the cities of Bukhara,  Samarkand,  Khwarazm,  and  Fergana  emerged  as  radiant  centers  of knowledge  and  civilization,  where  science,  literature,  philosophy,  and  theology flourished  under  the  patronage  of  enlightened  rulers  and  scholars.  Distinguished polymaths such as Al-Khwarizmi, Al-Farghani, Al-Farabi, Al-Biruni, Ibn Sina, Al-Bukhari, and Omar  Khayyam laid the foundational stones of modern mathematics, astronomy,  medicine,  and  philosophy.  Their  groundbreaking  discoveries,  empirical methodologies,  and  philosophical  rationalism  not  only  advanced  the  frontiers  of knowledge but also profoundly influenced the intellectual transformation of Europe during the later Renaissance. The Central Asian Renaissance thus stands as a vital bridge between the classical civilizations of antiquity and the modern scientific era, embodying humanity’s universal quest for truth, wisdom, and enlightenment.